Enhancement of undrained shear strength and compressibility behaviour of marine clay by biomineralization under electrokinetic method - Abdelrahman, Mousa Ahmed Hassan Saad (2020)
Marine clay soils imposed an instability problem under applied load due to the absence or limitation of its shear strength. This weakness of marine clay causes large settlements leading to failure of structures and loss of their efficiency and their working purposes. This problem typically occurs in the areas near to seashores and riverbanks. The presence of a large amount of water causes significantly large deformations and settlements, which then caused damage to the nearest structures and human safety. Accordingly, biomineralisation treatment under the electrokinetic (EK) effect has been a recent approach to stabilise the soil. Biomineralisation treatment shows a significant improvement in the undrained shear strength of weak soils, as proven by previous researches on sandy soils. It was also applied to clayey soils and showed a significant increase in undrained shear strength, but under EK effect due to permeability limitations and pores limited size to the size of bacteria cells. This method promises to stabilise soils efficiently without any side effects on the environment. However, there is no research on marine clay treatment using biomineralization under EK method. Also, there is no research investigated any alternative metal source to CaCl2 such as MgCl2. In addition, previous studies were focusing on increasing the undrained shear strength without considering the homogeneity of the treatment and reduction of its variation. So that, factors like distance and injection location should be considered to achieve better treatment of marine clay soil. In this study, an improved method of biomineralisation treatment under the electrokinetic effect was proposed and applied on marine clay to investigate the efficiency of this method. Bacteria, Bacillus pasteurii was used and was tested at three different cells concentration 2.00 × 107, 1.00 × 107 and 0.5 × 107 cells/ml. Two different metal sources were tested, which were CaCl2 and MgCl2 at seven different molarities; 0.00, 0.75, 1.00, 1.50, 2.00, 3.00 and 4.00 M while CO(NH2)2 was tested at four different molarities 1, 2, 3 and 4 M as the required source of carbonate ions. The efficiency of Microbial Induced Carbonate Precipitation (MICP) was investigated by applying 192 different combinations of bacteria, metal sources, and CO(NH2)2 for identifying optimum concentrations, which were B1C1aU1 and B1M1aU1 for CaCl2 and MgCl2 respectively. Both combinations were injected into soil specimens, where both shown a significant increment in undrained shear strength after 7 days of treatment from 4.17 kN/m2 to a range of 20 to 76 kN/m2. Both effects of distance between the two electrode cells and location of CO(NH2)2 injection were also investigated by using a physical model with dimensions of 1200 × 300 × 500 mm (L × W × H ). Three different distances investigated were 450, 600 and 750 mm between cathode and anode cells. Results show that undrained shear strength was inversely proportional to the distance. On the other hand, four different CO(NH2)2 injection locations which were at zero, L/4, 2L/4 and 3L/4 from cathode cell were tested. Results showed that undrained shear strength was inversely proportional to the CO(NH2)2 injection location from the cathode cell, but the variation in undrained shear strength along the treatment path between the two electrodes where it was decreasing as the CO(NH2)2 injection location getting far from the cathode. Eventually, numerical equations were derived to ease the prediction of concentrations of required materials for the targeted efficiency of MICP and for optimum treatment of marine clay where the equation Su = 53.862 - 1.534d - 17.305i - 0.045D - 0.023X could be used as a guideline and estimation for undrained shear strength after treatment by biomineralization under electrokinetic method for future research.